PENGARUH BERMAIN GAME ONLINE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XI IPS SMA NEGERI 8 PEKANBARU - Yanti, Suci Fajri; Gimin, Gimin; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to analyze the effect of playing online games on student learning outcomes in economic subjects in class XI IPS at SMA Negeri 8 Pekanbaru. The population of this study were all students who took economic lessons as many as 108 students. . Data were collected through questionnaires and documentation. The results showed (1) student learning outcomes were still low with an average of 78.75 with a KKM of 80. (2) the frequency of the types of online games most favored by students between non-economic online games, economic online games and online game competitions was playing games. online economy with the highest percentage of 17 and the percentage of 37.7%. based on the online game classification, the highest is free fire with an average number of 6.33. based on the online game classification, the highest is free fire with an average number of 6.33. For economic online games, the highest percentage is 13 with a percentage of 28.8% with the highest economic online game classification, namely billioners with an average number of 5. While online game competitions, the highest percentage is 15 and the percentage is 33.3% with game competition classification. The highest online is free fire with an average number of 8.6 (3) The results of the study are based on multiple linear regression with the equation HB = 64.293- 0.734 GONE- 0.644 GOE- 0.591 KGO means non-economic online games, economic online games, and online game competitions has a significant negative effect on learning outcomes. This happens because students tend to have a higher intensity towards online games and online game competitions than economic online games.Key Words : Play Online Games, Student Outcomes